1963
DOI: 10.2134/agronj1963.00021962005500050020x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Virus Diseases on Milling and Baking Properties of Wheat Grain and Flour and on Probable Nutritive Value of Forage Wheat1

Abstract: Synopsis Grain samples from wheat plants infected by soil‐borne‐mosaic or wheat‐streak‐mosaic virus had milling properties that were inferior to, protein quality and mixing properties that were equal to, and water absorption, protein content, and “as received” leaf volume that were distinctly superior to those of the corresponding controls. Forage samples of winter wheat varieties susceptible to and infected by wheat‐streak‐mosaic virus were significantly higher (0.1% level) in protein content than those of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, certain authors have reported on the effects of some viruses about the growth and yield of wheat (MCKINNEY 1953, LAL and SILL 1959, SLYKHUIS 1962, Sund and ToSic 1966, ATKINSON and GRANT 1967, BELJANCIKOVA and PRIDANCEVA 1967. FINNEY and SILL (1963) studied the effect of virus infections on milling and baking qualities of grains from infected wheat plants. PANIC!…”
Section: Introductionmentioning
confidence: 99%
“…However, certain authors have reported on the effects of some viruses about the growth and yield of wheat (MCKINNEY 1953, LAL and SILL 1959, SLYKHUIS 1962, Sund and ToSic 1966, ATKINSON and GRANT 1967, BELJANCIKOVA and PRIDANCEVA 1967. FINNEY and SILL (1963) studied the effect of virus infections on milling and baking qualities of grains from infected wheat plants. PANIC!…”
Section: Introductionmentioning
confidence: 99%
“…It is most prevalent in the central Great Plains of the USA, where it destroys a significant percentage of both the spring and winter wheat crop annually (Wiese, 1987). In addition to yield losses, WSMV reduces test weight and milling quality (Finney and Sill, 1963) The disease was first identified in Montana in 1954, and Montana growers have experienced major outbreaks in 1964, 1981, 1993, and 1994 (Bamford et al, 1996). The 1993 outbreak resulted in an estimated $12.7 million damage (Fowler, 1998).…”
mentioning
confidence: 99%